Pemanfaatan Limbah Medis Padat Infeksius RSUD Arifin Achmad Pekanbaru Dengan Teknik Solidifikasi Sebagai Campuran Batako - Bunga Fitriani Gumadita; Syaiful Bahri; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Hospital solid medical waste contain hazardous and toxic materials. One way to manage solid medical waste is a mixed hospital as one of the ingredients in the manufacture of concrete blocks. The purpose of this study was to test the initial testing and the final content of cadmium (Cd) and chromium (Cr) heavy metals through the test the concentration of heavy metals, and to test the compressive strength of concrete blocks. In this research, the B3 waste treatment method using solidification technology by varying the 0%, 10%, 20%, 30% and drying time 14, 21 and 28 days and the test concentrations of heavy metals. The results showed that in terms of compressive strength 28 days, brick with a variation of 10% of age 14 days 105 kg/ cm2, 10% aged 21 days 135 kg/cm2 and 10% u it 28 days to 200 kg/cm2 where it is strong pressure to rise. From the test results are known concentrations of heavy metals mostly heavy metal content is 30% at 0.00034 ppm Cd of 0.180 ppm after disolidifikasi. Likewise, 30% of heavy metals in Cr is 8.509 ppm 0,044 ppm of immobilized so well that solid infectious medical waste can be used as a mixture of brick that is safe for the environment.Keywords: Infectious Medical Waste Solid, brick, Compressive Strength, Solidification, Heavy Metal Concentration Test.